Understanding the formation and evolution of galactic superbubbles - Suárez López, Osmer Alexander (2024)
Galactic superbubbles are lobe-like structures that are created by intense episodes of star formation, occurring in the discs of spiral galaxies. Star formation processes are important feedback mechanisms in such galaxies as they permit the exchange of gas and dust between the interstellar and circumgalactic media. Observationally, superbubbles are detected via emission or absorption line studies of atomic and molecular species, but telescope information is projected, so numerical simulations are needed to understand their 3D structure. In this thesis we resort to hydrodynamical simulations to numerically study the 3D structure of such superbubbles. We include stratified galactic atmospheres using analytical prescriptions, which are then used as initial conditions in our numerical models. Our simulations explore the effect of changing the turbulence strength parameter (σ_t), which controls the disc morphology, its initial cloud distribution, and the atmosphere kinematical profile. We find that galactic superbubbles arise from interactions between SF winds and the ISM in the disc. Their formation is favoured by higher σ_t values, as they allow for a better channeling mechanism than low σ_t. At the end, σ_t> 60, km s^(-1) are needed to produce superbubbles that resemble those found in the Galactic centre of the Milky Way. Recent studies show that the Galactic centre harbours a chimney in the northern direction, which currently lacks a theoretical explanation. This study contributes to the understanding of this feature.